Determinant Factors of Digital Financial Literacy: A Study of Women Entrepreneurs - Mardhiyaturrositaningsih, Mardhiyaturrositaningsih; Muhammad Luqman Hakim (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Micro, Small, and Medium Enterprises contribute to 61% of economic growth in Indonesia. The financial gap in MSMEs financing is based on data from the Ministry of Cooperatives and MSMEs. Women comprised the majority of MSMEs (61.8%). There were 38.03% literacy problems and 76.19% inclusion criteria. This study investigated the digital financial literacy of female entrepreneurs in Central Java. A survey method was used in this study with 100 women entrepreneurs. Digital Financial Literacy is identified in the three OECD components: Digital Financial Knowledge, Digital Financial Behavior, and Digital Financial Attitudes. The results of this study indicate that the average respondent had sufficient knowledge of digital finance. Limited knowledge of insurance services and capital markets. Meanwhile, the digital financial behavior and attitude components show that digital security protection measures are still low. It is hoped that digital financial literacy can support female entrepreneurs in developing their businesses.